SAFETY OF MEDICINAL PLANTS: AN IMPORTANT CONCERN - SHAZIA TABASUM; SWATI KHARE (International Journal of Pharma and Bio Sciences, 2016)
Medicinal plants are natural sources of drugs used to cure various disorders of mankind. These serve as reliable medicine because of the presence of various biochemical substances. Herbal drugs gained fame in health care all over the world, especially in developing countries as these are locally accessible, economical and are having lesser side effects. But the natural origin may not be a sign of their safety. A limited number of available evidences indicated that adverse effects associated with herbal drugs are fewer. They may cause severe effects on the vital organs of human body chiefly because of self - medication. There is also an inadequate data available for most of the herbal medicines revealing their toxicology, safety and efficacy. Thus, efforts should be taken to ensure the benefits as well as health hazards associated with the herbal remedies.